Radiation-Induced Heart Disease: A Clinical Update - Syed Wamique Yusuf; Shehzad Sami; Iyad N. Daher (Cardiology Research and Practice)
Cardiovascular diseases and cancer are the two leading causes of morbidity and mortality worldwide. Improvement in cancer therapy has led to increasing number of cancer survivors, some of whom may suffer from adverse cardiovascular effects of radiation therapy. Longterm followup is essential, as the cardiac complication may manifest years after completion of radiation therapy. In this paper, we have discussed the cardiovascular effects of radiation therapy.